The Value of the Pedagogical Dialogue in the “Knowledge Society” - Edward Torończak (Paedagogia Christiana, 2014)
Placing pedagogical dialogue in a personalistic context indicates the significance of upbringing in education. A concept of the ‘knowledge-based economy’ promoted by some politicians, in which ‘transmission of knowledge’ can lead to marginalization of upbringing itself. In this context, pedagogical dialogue embedding the issue of upbringing in education seems particularly important. The pedagogical dialogue in its essence brings about an agreement, meeting and cooperation between the teacher (the ‘fosterer’) and the student (the ‘fostered one’). It is essential inasmuch as it enables to re-construct the community of teachers and students, where school becomes the ground for meeting and participation in social life. Not only should it be beneficial for individuals but also for the society as a whole. In this perspective, pedagogical dialogue becomes essential in the process of attitude formation of responsibility for personal development of each individual and coherence creation of ‘school community’.